Dataset and code for comparing structural variables from terrestrial LiDAR, digital photogrammetry and field inventory in forest and agroforestry landscapes - Onyiriagwu, Magnus; Zemp, Clara; Nereoh, Leley; Ngaba Waye Taroum, Caleb; Macharia, Anthony; Muchiri, Henry; Kisiwa, Abdalla (My University, 2025)
The dataset contains the scripts and the datasheet (see the Zenodo link) used for the comparative analysis of vegetation structural characteristics of Terrestrial laser scanning (TLS), UAV-based digital aerial photogrammetry (DAP), and ground-based field inventory (Field) in tropical landscapes.